2009
DOI: 10.1021/cm902094q
|View full text |Cite
|
Sign up to set email alerts
|

B Cation Ordered Double Perovskite Ba2CoMo0.5Nb0.5O6-δ As a Potential SOFC Cathode

Abstract: This paper reports the evaluation of the cubic B site cation-ordered double perovskite system Ba2Co2−x (Mo1/2Nb1/2) x O6, resulting in the single phase composition Ba2CoMo0.5Nb0.5O6−δ (BCMN) with a mixed Co charge state stabilized by a combination of Mo and Nb doping as a new mixed conductor with potential SOFC cathode applications. X-ray, neutron, and electron diffraction show that hexagonal intergrowths found in multiple phase samples at lower Mo/Nb contents are suppressed in BCMN, which has large domains of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 58 publications
(96 reference statements)
2
69
0
Order By: Relevance
“…The inflections on the electrical conductivity curves at 600 1C are attributed to the release of lattice oxygen and the thermal reduction of Fe 4 þ to Fe 3 þ and Fe 3 þ to Fe 2 þ on heating. The electrical conductivity values of the SFT sample are 2.83-2.33 S cm À 1 in the temperature range of 600-800 1C and reaches a maximum value of 2.83 S cm À 1 around 600 1C, which is much higher than that of Ba 2 CoMo 0.5 Nb 0.5 O 6 À δ cathode [42]. It agrees well with the previously reported in the literature [38].…”
Section: Electrical Conductivitysupporting
confidence: 91%
“…The inflections on the electrical conductivity curves at 600 1C are attributed to the release of lattice oxygen and the thermal reduction of Fe 4 þ to Fe 3 þ and Fe 3 þ to Fe 2 þ on heating. The electrical conductivity values of the SFT sample are 2.83-2.33 S cm À 1 in the temperature range of 600-800 1C and reaches a maximum value of 2.83 S cm À 1 around 600 1C, which is much higher than that of Ba 2 CoMo 0.5 Nb 0.5 O 6 À δ cathode [42]. It agrees well with the previously reported in the literature [38].…”
Section: Electrical Conductivitysupporting
confidence: 91%
“…[21,25] Recently,N b 5 + has been widely doped into different parent perovskite cathode materials to stabilize the cathode-favored cubic structure and even give ab oost to the ORR activity of the cathodes. [9,[26][27][28][29][30] For example, Zhoue tal. [13] reported ah ighly active SOFC cathode at temperatures below 600 8C after substituting Nb 5 + into Sr(Sc,Co)O 3Àd perovskite oxide,a nd many researchers also substituted Nb 5 + into milestone cathodes, such as (La,Sr)(Co,Fe)O 3Àd [28] and (Ba,Sr)(Co,Fe)O 3Àd .…”
Section: Introductionmentioning
confidence: 99%
“…24,27 Briefly, sample powder is placed on a quartz frit within a quartz tube plug flow micro-reactor. Before each isotope exchange experiment, the sample was pre-treated under 16 O 2 stream at 700 • C in order to ensure that the sample did not contain excess 18 O 2 and that the surface was clean. Based on BET surface area measurements (nitrogen sorption isotherms, Micromeritics ASAP 2020 surface area and porosimetry analyzer, using the standard BET method), each sample was weighed to yield a uniform surface area of 0.1 m 2 .…”
Section: Physical Electrical and Electrochemical Characterization-mentioning
confidence: 99%
“…The high temperature cubic phase of these SrCoO 3-δ shows very promising oxygen reduction catalytic properties, however above 900 • C this phase is structurally not stable, and exhibits drawbacks mainly through large thermal expansion coefficients and high reactivity with yttria-stabilized zirconia electrolytes. [17][18][19][20] In previous works, Zhou et al 21,22 reported enhanced single phase stability and charge transfer properties of Nb-doped SrCoO 3-δ . In particular, partial substitution of the B-site by high valance cations should lead to a smaller discrepancy in the ionic radius between A-and B-sites, and eventually to stabilized cubic structure.…”
mentioning
confidence: 99%